Performativité et éthique de la remédiation dans Dora Bruder, de Patrick Modiano - Élisabeth Routhier (Itinéraires)
What exactly do we mean by “disappearance”? Is it an event? A figure? The end of an existence? For Patrick Modiano, disapearance is rather a starting point for an act of writing that slips through a sum of mediations. The inextricable link between disappearance and (re)mediation is in fact the basis upon which I build my analysis of Dora Bruder’s opening pages from an intermedial stance. Ethical remediation and performativity will be the core concepts to analyse Modiano’s writing through the lens of disappearance.